Soviet samizdat : imagining a new society - Komaromi, Ann (Ithaca, NY : Northern Illinois University Press, an imprint of Cornell University Press, 2022)
"Traces the emergence and development of samizdat as an uncensored system for making and sharing texts. Based on research of the underground journals, bulletins, art folios and other periodical editions produced in the Soviet Union from the mid-1950s to the mid-1980s, this book analyzes the role of samizdat in fostering new forms of imagined community among Soviet citizens"--
Introduction : Samizdat and Underground Publics in the USSR -- Samizdat and the Historical Self -- Giving Voice to Truth in Samizdat -- Imagining Time in Samizdat -- Spaces of Samizdat Sociality -- Conclusion : Samizdat and the Contradictions of Soviet Modernity.
Includes bibliographical references (pages 255-284) and index.
Keywords: Underground literature -- Social aspects -- Soviet Union; Underground press publications -- Social aspects -- Soviet Union; Underground periodicals -- Social aspects -- Soviet Union; Literature and society -- Soviet Union; Soviet Union -- Politics and government -- 1953-1985.